Marine fouling community in the Eastern harbour of Alexandria, Egypt compared with four decades of previous studies - RAMADAN, SH.E.; KHEIRALLAH, A.M.; ABDEL-SALAM, KH.M. (Mediterranean Marine Science, 2006)
The aim of the present study is to compare the fouling communities between the years 1960 and 1999 in the Eastern harbour of Alexandria, Egypt and to study the main factors that may be controlling these communities. This comparison is based on monthly durations of panel immersion. By using roughened white polystyrene test panels (12.5x12.5 cm), monthly samples of marine fouling were collected from the harbour from October 1998 through September 1999. It is clear that a remarkable variation in number and diversity of fouling communities throughout the last four decades is evident. The minimum diversities were recorded during the studies of 1960 and 1970 (19 and 20 species respectively), while the maximum diversity (35 species) was achieved during the 1991 study. Moreover, a small shift among the four dominant groups (Polychaeta, Cirripedia, Bryozoa and Amphipoda) was noted during the four decades of the studies. The present comparison indicated that many factors may contribute to this variation, of which nutrient enrichment is the most important and the nature of the applied test panel is lees so.